The free fasciocutaneous infragluteal (FCI) flap: Outcome and patient satisfaction after 142 breast reconstructions. Issue 4 (April 2016) - Struckmann, Victoria; Peek, Alberto; Wingenbach, Oliver; Harhaus, Leila; Kneser, Ulrich; Holle, Giesbert
Summary: Background: The free fasciocutaneous infragluteal flap (FCI) is relatively rarely used for autologous breast reconstruction; however, it is a good option for thin patients. The outcome of 142 FCI flaps for breast reconstruction is presented here. Materials and methods: Between January 2008 and December 2013, 142 patients underwent unilateral breast reconstruction with the FCI flap. Outcome analysis, scar quality, postoperative pain, and patient satisfaction were evaluated by questionnaires and established scores. The tactile sensitivity of the breast was measured by the Semmes–Weinstein monofilament test. Results: The mean age was 45.4 ± 9.17 (23–69) years, the mean follow-up was 40.2 (12–58) months, and the rate of flap loss was 0.7% ( n  = 1). Postoperative pain was stated with 4.2 ± 2.5 points on the visual analog scale (VAS). The quality of breast reconstruction was rated "very good" ( n  = 43) or "good" ( n  = 33) by 71% of patients, and 89% ( n  = 96) of patients would recommend this procedure to others. As expected, postoperative mobility was achieved in 80% ( n  = 86) of patients and some obtained this even earlier. Forty-seven patients presented for follow-up examination (44%). Scars on the reconstructed breasts were rated with 1 ( n  = 16) or 2 ( n  = 22) points in 81% and scars at the infragluteal donor site with 2 ( n  = 17) or 3 ( n  = 25) points on the Vancouver scar scale (VSS) in 89%. Patients subjectively stated having better sensitivity of the reconstructed breast than measured objectively by monofilaments. Conclusion: The FCI flap is a safe method for breast reconstruction due to a low percentage of flap loss and complications. Good patient satisfaction along with fast postoperative mobilization can be achieved. The FCI flap should be considered a suitable alternative for autologous breast reconstruction.